A DESCRIPTIVE STUDY ON PREGNANCY AND CHILDBIRTH OF ONE STUDENT ONE CLIENT (OSOC) PATIENTS OF MIDWIFERY STUDENTS OF POLYTECHNIC BANJARNEGARA - Dewie Sulistyorini; Barni Barni (Siklus : Journal Research Midwifery Politeknik Tegal, 2020)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (MMR) are indicators of a country's welfare. In 2018 there were 421 maternal mortality cases in central java. This number was a decrease compared to the mortality case in 2017, as many as 475 cases.  This study aimed to identify health conditions during pregnancy and the childbirth period of the patients of One Student One Client (OSOC) in Polytechnic Banjarnegara. A descriptive study conducted at Basic Emergency Neonatal Obstetric Services (PONED) in Banjarnegara District in March - April 2019 to 26 pregnant women. The results showed that most of the respondents classified the low-risk age group as 21 respondents (81%). There are 15  respondents (58%) classified to low-risk pregnancy distance category, 24 respondents (92%) are classified to normal gestational age category, and average birth weight category. It is recommended to ensure maternal health during pregnancy and childbirth is always well monitored. Ensuring mothers can access quality services in health services. It is necessary to have continuous assistance from students in OSOC activities as an extended arm of health workers. Keywords: Pregnancy, Childbirth, Health Client.